Stories Told and Untold: Confidentiality Laws and the Master Narrative of Child Welfare - Fraidin, Matthew I. (2010)
In most states, child welfare hearings and records are sealed or confidential. This means that by law, court hearings and records may not be observed. The same laws and court rules also preclude those who are authorized to enter and watch from discussing anything learned or observed in a closed courtroom or from a sealed court record with anyone not involved in the case. It is the restriction on speech—on telling stories about child welfare—with which this Article is concerned. The master narrative of child welfare depicts foster care as a haven for child-victims savagely brutalized by “deviant,” “monstrous” parents. Notwithstanding this shared public understanding, however, most children in foster care have experienced, or are alleged to have experienced, neglect—deprivation of food, clothing, shelter, education, or another necessity of life—not physical abuse. There is also a growing understanding that some children in foster care ought not to be there at all. In addition, research and experience indicate that many maltreated children would be better off if simply left at home—with those responsible for the maltreatment—rather than placed in foster care. This Article argues that confidentiality laws perpetuate the inaccurate master narrative, and preclude other stories from informing or influencing that narrative. Stated simply, laws prohibiting the discussion of child welfare cases silence a vast number of stories. By their terms, these laws define the stories that may not be told, and the putative storytellers who may not speak, while designating as acceptable other stories and other voices. The unchallenged dominance of the inaccurate, law-sanctioned narrative affects even those involved in child welfare as a profession, and by affecting their worldview, diminishes the quality of care provided to children. The laws that require silence outside the courtroom permit the acceptance of pervasive dysfunction in child welfare, and affect the administration of justice inside the courtroom